PENENTUAN SOLUSI NUMERIK PERSAMAAN BKdV DENGAN METODE BEDA HINGGA - Sehah, Sehah; Aminuddin, J. (BERKALA FISIKA, 2009)
The innovative knowledge for modelling of the wave propagation is solitary waves. The dynamical model of solitary wave represented in Korteweg de Vrise (KdV) equation form. In this modelling assumed that the KdV equation has not perturbation sign, so called Basic Korteweg de Vries (BKdV) equation.  This modelling begins from expressing of the BKdV equation into to discrete form as its linear form using implicit scheme for finite difference method. Then, it linear form constructed into matrix form.  The solution of matrix form determined using Gauss-Jordan method for resulting of the numerical solution of the BKdV equation. numerical solution was representing on the surface-graphic for the wave envelope as representation of the dynamical non linear in the water.  This modelling results indicating that the wave envelope  was has distortion of initial amplitude  on longstanding of time.  It indicate  that the fluid energy was has distortion on longstanding of time. Key Word: Soliton, KdV, Numerical, Wave, Envelope